2016
DOI: 10.1021/jacs.6b07096
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Pseudoirreversible Binding of Amantadine to the M2 Proton Channel

Abstract: The M2 proton channel of influenza A virus is an integral membrane protein involved in the acidification of the viral interior, a step necessary for the release of the viral genetic material and replication of new virions. The aim of this study is to explore the mechanism of drug (un)binding to the M2 channel in order to gain insight into the structural and energetic features relevant for the development of novel inhibitors. To this end, we have investigated the binding of amantadine (Amt) to the wild type (wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 94 publications
3
36
0
Order By: Relevance
“…The binding trajectories of the M2 channel blockers in the channel pore of S31 M2 showed that amantadine first binds to two of the four Asp24 residues via salt bridges to yield a metastable conformation separated by a high free energy barrier. Previous conventional and multiple‐walkers well‐tempered metadynamics simulations of amantadine unbinding pathway from S31 M2 have shown that Asp24 interacts with amantadine and this binding mediates the amantadine flipping at the entrance of channel pore . Therefore, it is possible that these data support the hypothesis that the metastable binding of amantadine to Asp24 is important in forming a thermodynamically favored binding of amantadine to the channel pore of S31 M2.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The binding trajectories of the M2 channel blockers in the channel pore of S31 M2 showed that amantadine first binds to two of the four Asp24 residues via salt bridges to yield a metastable conformation separated by a high free energy barrier. Previous conventional and multiple‐walkers well‐tempered metadynamics simulations of amantadine unbinding pathway from S31 M2 have shown that Asp24 interacts with amantadine and this binding mediates the amantadine flipping at the entrance of channel pore . Therefore, it is possible that these data support the hypothesis that the metastable binding of amantadine to Asp24 is important in forming a thermodynamically favored binding of amantadine to the channel pore of S31 M2.…”
Section: Discussionsupporting
confidence: 54%
“…Conventional MD and stirred MD simulation studies have shown that, although amantadine specifically binds to S31 M2 through amino acid residues such as Val27, Ala30 and His37, the amino group of amantadine oppositely faces up toward the N‐terminus and does not have specific binding residues in the channel pore of N31 M2; thus, water molecules occupy space in the channel pore and proton conduction is not impaired . Conventional and multiple‐walkers well‐tempered metadynamics simulations have revealed that amantadine transiently binds to Asp24 during the unbinding pathway of amantadine from the channel pore of S31 M2 , suggesting that Asp24 is one of the metastable binding sites located at the entrances of channel pores. However, the details of the kinetics of binding of amantadine to M2 remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The Well‐Tempered variant of Metadynamics (WTmetaD) was performed in the NVT ensemble for a total simulation time of about 150 ns. The software NAMD‐2.10 patched with PLUMED‐2.1 was used to execute the enhanced sampling calculations. Two collective variables (CVs) were chosen to efficiently sample the different Ni(II)‐complexed configurations.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast with the C open M2TM structure [27][28][29] and Amt-bound C open M2TM structure 28 at pH 5 in which the MD simulation of M2TM-Amt complex reveals multiple anions simultaneously inside the pore in the Q3 or Q4 state, 28 or in the MD simulation of M2AH-Amt complex, with M2AH in the Q2 state in which the presence of more than one chloride anion was suggested as possible. 30 (A) Recently, the potential of mean force (PMF) for Trp41 dihedral χ 2 was calculated and concluded that t-105 rotamer corresponds to a metastable state, while t-90 rotamer is energetically preferred. 26 The ssNMR structure of M2AH (PDB ID 2L0J) has the rotamers for all Trp41 with χ 2 = 105º.…”
Section: Ingredients Of Pore In M2 Protein Complexesmentioning
confidence: 99%